Payments for Agrobiodiversity Conservation Services (PACS): Current status and implications for the conservation of threatened varieties of quinoa in Puno, Peru - Drucker, Adam G.; Arpazi-Valero, Kleny; Ramírez, Marleni; Medina, Tulio (2021)
Current status and implications for the conservation of threatened varieties of Quinoa in Puno, Peru